Integrated well pad development scheduling with steam injection control in steam-assisted gravity drainage. (May 2020) - Mohankumar, Yashas; Li, Zukui; Huang, Biao
Highlights: Integrated optimization between long term reservoir development and short term operations for SAGD process. Mixed integer linear optimization based scheduling model and nonlinear optimization based economic model predictive control formulation. Shrinking horizon based scheduling level and rolling horizon based control level implementation. Closed loop integration for multi-scale decision making leads to superior economic benefits in reservoir operations. Abstract: In this paper, we study the problem of integrated well pad development scheduling with nonlinear model predictive control based steam injection in steam-assisted gravity drainage (SAGD). The scheduling problem has been modeled as a mixed-integer program to find optimal development sequence and timing of multiple well-pads. Model predictive control problems are solved to find optimal steam injection profile such that the reservoir is under control. The integrated problem is solved using open-loop and closed-loop methods: (1) scheduling problem is only solved at the beginning of project operation, (2) Scheduling problem is solved every year with shrinking horizon implementation, and (3) shrinking horizon implementation of scheduling with reservoir model update based on feedback from control level. Simulation results demonstrate the benefits of closed-loop integrated scheduling and control: the NPV increase is 19%.